Design of Augmented Reality Technology as an Educational Medium for Facial Skincare among Adolescents Based on Android - Harahap, Hazarul Rahmat Nur; Khairunnisa, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
In the digital era, teenagers are more focused on the health of their facial skin, yet many experiment with different skincare products without comprehending their ingredients or how appropriate they are, which poses risks of side effects. Education on safe and suitable skincare is essential to reduce these risks. This research intends to create a facial skincare educational app utilizing Augmented Reality (AR) through the Marker-Based Tracking technique. The app was created with Unity and Vuforia to showcase interactive 3D models that present skin types and suitable skincare items. The phases employed in this research development utilized the MDLC approach: Concept, design, material gathering, production, testing, and distribution. The findings indicated that the application performed effectively on Android devices, 3D objects displayed properly in relation to markers, all buttons worked correctly, and 81.1% of participants perceived the application as beneficial. Consequently, this AR application serves as an interactive educational tool that improves comprehension of skincare in a visual, engaging, and easily accessible manner.